Breaking of ensembles of linear and nonlinear oscillators - Buts, V.A. (Вопросы атомной науки и техники, 2017)
Some results concerning the study of the dynamics of ensembles of linear and nonlinear oscillators are stated. It is shown that, in general, a stable ensemble of linear oscillator has a limited number of oscillators. This number has been defined for some simple models. It is shown that the features of the dynamics of linear oscillators can be used for conversion of the low-frequency energy oscillations into high frequency oscillations. The dynamics of coupled nonlinear oscillators in most cases is chaotic. For such a case, it is shown that the statistical characteristics (moments) of chaotic motion can significantly reduce potential barriers that keep the particles in the capture region. Изложены некоторые результаты исследования динамики ансамблей линейных и нелинейных осцилляторов. Показано, что в общем случае устойчивый ансамбль линейных осцилляторов имеет ограниченное число осцилляторов. Для простых моделей определено это количество. Показано, что особенность динамики линейных осцилляторов может быть использована для преобразования энергии низкочастотных колебаний в высокочастотные. Динамика связанных нелинейных осцилляторов в большинстве случаев хаотична. В этом случае показано, что статистические характеристики (моменты) хаотического движения могут существенно уменьшать потенциальные барьеры, которые удерживают частицы в области захвата. Викладено деякі результати дослідження динаміки ансамблів лінійних та нелінійних осциляторів. Показано, що в загальному випадку стійкий ансамбль лінійних осциляторів має обмежене число осциляторів. Для простих моделей визначена ця кількість. Показано, що особливість динаміки лінійних осциляторів може бути використана для перетворення енергії низькочастотних коливань у високочастотні. Динаміка пов'язаних нелінійних осциляторів у більшості випадків хаотична. У цьому випадку показано, що статистичні характеристики (моменти) хаотичного руху можуть істотно зменшувати потенційні бар'єри, які утримують частинки в області захвату.